Ability of RecA protein to promote a search for rare sequences in duplex DNA. - Honigberg, S M (1986)
RecA nucleoprotein filaments found homologous targets even when the latter was mixed with 200,000 times as much heterologous duplex DNA. By contrast, mixing of the single-stranded probe with only 100 times as much heterologous single strands markedly reduced the rate of finding homologous duplex molecules. Titration of the reaction with different proportions of homologous single-stranded DNA distinguished a condition under which the search for homology itself was rate limiting from a condition under which some later step was limiting. Less than 1 min was required to scan 6.4 kilobase pairs of duplex DNA for homology to a RecA-coated single strand of the same size, but these experiments revealed that rapid searching by RecA nucleoprotein filaments was largely confined to neighboring duplex molecules. These observations provide guidelines for the use of RecA protein in locating rare sequences in complex mixtures of duplex DNA, and we describe a simple protocol by which rare sequences can be rapidly enriched at least a thousandfold.